IMPLEMENTASI PROGRAM SEKOLAH PENCETAK WIRAUSAHA TERHADAP MINAT BERWIRAUSAHA SISWA SMKN 1 CIMAHI - Hurinnabila Arfah; Subali Subali (Economic Education, University of Jember, 2021)
Program Sekolah Pencetak Wirausaha (SPW) is a program of the Directorate of Vocational Development which aims to grow and develop student entrepreneurship interest. As it is known that vocational high school graduates are graduates who are prepared to become an independent generation, ready to work, and have have entrepreneurial skills. But, These empirical conditions are contradictory, seen from the Open Unemployment Rate in the education sector, vocational high school is the second largest contributor to unemployment. The solution from the government is the launch of Program Sekolah Pencetak Wirausaha (SPW) for vocational high school student. Therefore, the purpose of this research is to find out how much influence the implementation of the Program Sekolah Pencetak Wirausaha (SPW) has on the Entrepreneurial Interests of Vocational high school 1 Cimahi students. This research uses a quantitative approach with a sample of 30 students. The data analysis technique used is a simple regression test by analyzing the two variables, but before that a prerequisite test is applied. The results of the analysis explain that the Program Sekolah Pencetak Wirausaha (SPW) has a positive influence on students entrepreneurial interest by 40.9%, it means that the program Sekolah Pencetak Wirausaha (SPW) has a positive and significant influence on students entrepreneurial interests.